PENATALAKSANAAN AKUPUNKTUR, TUINA CHUZHEN DAN FOOD THERAPY BERBASIS TCM PADA INFEKSI TORCH VIRUS PADA MASA KEHAMILAN - Yelini Fan Hardi; Stella Maris; Dewi Lelonowati Tri Mustariningrum (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2022)
Background :Congenital anomalies like hydrocephalus, chorioretinitis, hepatospenomegaly, congenital heart disease (CHD), and others are frequently present in newborns in Indonesia. Women who are planning to become pregnant or who are expecting may contract one of the TORCH infections (Toxoplasma, Other Disease, Rubella, Cytomegalovirus, and Herpes Simplex Virus). Objective: Knowing the outcomes of the treatment of torch virus infection during pregnancy using acupuncture, tuina chuzhen, and TCM-based food therapy Method : The technique that involves giving patients or clients direct instruction or demonstration Result : Acupuncture is used to treat pregnant TORCH patients if there is a risk of miscarriage in order to keep the Ren Mai and Chong Mai meridians, strengthen the spleen, and strengthen the kidneys. Suggestion : immediately take appropriate action in accordance with knowledge, and if required, refer to a more knowledgeable Expert Team Keywords : TORCH, Acupuncture, Tuina Chuzhen, Pregnancy, Traditional Chinese Medicine Therapy